The Impact of Residential Location and Settlement Hierarchy on Ecological Footprint. (October 2014) - Poom, Age; Ahas, Rein; Orru, Kati
This study addresses the question of how residential location influences the ecological footprint (EF) of households. The type and location of settlements are considered one of the key determinants of the patterns of mobility and consumption, and their associated environmental load. As different settlement types bring different consumption intensities causing adverse environmental effects, the search for the best settlement structure is complicated. We study the environmental load of 16–17-year-old high school students from thirty randomly selected schools located across Estonia by means of a questionnaire survey. The study finds that the EF of high school students is significantly affected by the position of their residence in the settlement hierarchy as a result of different levels of affluence, density, and accessibility to goods and service, all of which vary spatially. Students from the metropolitan area of Tallinn tend to place a larger load on the environment and have higher EF values than students from the rest of Estonia. In addition, higher per capita income and larger living spaces tend to increase the footprint of these students. The results show that the strong sociospatial stratification of Estonian residents, symptomatic of a transitional society, is evident also in their environmental consumption load and mobility habits.